Evaluation of Indoor Hockey Sports Achievement Development - Muhamad Zainal Abidin; Setya Rahayu; Harry Pramono (Universitas Negeri Semarang, 2025)
https://drive.google.com/file/d/1Lwm6s1btfhukmerB-B549wU4FjGInbEH/view?usp=sharing